Impaired inhibitory processing: a new therapeutic target for autism and psychosis?. (June 2021) - Heinze, Kareen; Barron, Helen C.; Howes, Emma K.; Ramaswami, Mani; Broome, Matthew R.
Summary: In the healthy brain, homeostatic balance between excitation and inhibition maintains neural stability. Reduced inhibition may explain shared symptoms observed in autism and psychosis. Here we review evidence suggesting that altered levels of gamma-aminobutyric acid (GABA) may underlie both disorders, providing a potential cross-diagnostic therapeutic target.